Optimizing Student Health and Fitness Through Healthy Lifestyle Education and Physical Activity at the Muhammadiyah Kampung Bharu Guidance Studio, Kuala Lumpur, Malaysia - Nurfardiansyah Burhanuddin; Yusriani; Tutik Agustini; Raihan Zainal; Rasti Rezkyana Qurnia Suparman (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Fitness physical important owned because with fitness relative physical​ good so somebody will own good health too. Healthy Lifestyle and Activities Physique moment This is issue crucial, especially for children Indonesian migrants in Sanggar Guidance of Muhammadiyah Kampung Baru, Kuala Lumpur, Malaysia, which is facing problem in the form of the low awareness about importance pattern life healthy among​ students and parents, facilities-sports at school No managed with good, and not there is an ongoing program for educate student about habit life healthy. This program aim-for optimize health and fitness student through education pattern life healthy and active physical based games​​ traditional that has known among​ students. With approach participatory, activities carried out covering education draft pattern life healthy, health soul and consciousness self, and intake pattern Eat healthy and nutritious balanced, and sport sustainable game traditional as a learning medium. Pre-test and post-test evaluations show improvement significant changes that occurred in knowledge (40% to 94%), attitudes (55% to 85%), and actions/practices (27% to 90%) related to draft pattern life health and fitness physical. Program outputs include educational booklets, cards monitoring, as well as publication scientific. This program also contributes to the achievement of Key Performance Indicators (KPI) of universities tall through involvement students and lecturers in devotion impacted communities. This effort succeed-optimize Health and Fitness Student through Healthy Lifestyle Education and Activities Physical, with recommendation for continue involvement community and expand support so that the program's impact can be maintained and improved.